Localized Augmentation of Net Precipitation to Shrubs: A Case Study of Stemflow Funneling to Hummocks in a Salinity-Intruded Swamp - Allen, Scott T.; Conner, William H. (Frontiers in Forests and Global Change, 2021)
The interception of precipitation by plant canopies can alter the amount and spatial distribution of water inputs to ecosystems. We asked whether canopy interception could locally augment water inputs to shrubs by their crowns funneling (freshwater) precipitation as stemflow to their bases, in a wetland where relict overstory trees are dying and persisting shrubs only grow on small hummocks that sit above mesohaline floodwaters. Precipitation, throughfall, and stemflow were measured across 69 events over a 15-month period in a salinity-degraded freshwater swamp in coastal South Carolina, USA. Evaporation of intercepted water from the overstory and shrub canopies reduced net precipitation (stemflow plus throughfall) across the site to 91% of gross (open) precipitation amounts. However, interception by the shrub layer resulted in increased routing of precipitation down the shrub stems to hummocks – this stemflow yielded depths that were over 14 times larger than that of gross precipitation across an area equal to the shrub stem cross-sectional areas. Through dimensional analysis, we inferred that stemflow resulted in local augmentation of net precipitation, with effective precipitation inputs to hummocks equaling 100-to-135% of gross precipitation. Given that these shrubs (wax myrtle, Morella cerifera) are sensitive to mesohaline salinities, our novel findings prompt the hypothesis that stemflow funneling is an ecophysiologically important mechanism that increases freshwater availability and facilitates shrub persistence in this otherwise stressful environment.